Pembelajaran keterampilan membaca dengan menggunakan pendekatan komunikatif di MA IBADURRAHMAN - Nurul Hana Mustofa (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah, 2020)
Abstrac Communicative approach is a centralized approach to communication skills in learning. This is a new breakthrough for learning, as it combines some strategies. Accustoming self-practice uses pure and creative language. The purpose of this learning is to give learners the opportunity to use Arabic in spontaneity, pure and creative by giving attention to the grammatical rules of the language. Therefore, the learning of Kalam direction is suitable when using communicative approaches, because it is an approach that requires communication between speakers of languages. This research aims to describe the learning process of Kalam direction by communicative approach at MA Ibadurrahman Islamic Senior High School of Malang. The results showed that the learning process of Kalam began to start until the end consisted of; Teachers who are able to carry out the study with communicative approaches, good learning objectives of kalam, the suitability of learning materials used, the suitability of the learning activity used and the presence of consistent evaluation. Keyworrd: Teaching, Spiking Skill, Communicative approach الملخص المدخل الاتصالي يتركز على الكفاية الاتصالية عند تعليم اللغة. هذا المدخل مخترق جديد لتعليم اللغة. لأنه مخالط بين بعض الاستراتيجيات ببعض وهو ممارسة استخدام اللغة عفيفيا وإبداعيا. الهدف من هذا المدخل هو إعطاء المتعلمين الفرصة لاستخدام اللغة العربية في حلة طبيعية مع عفيفية وإبداعية، وذلك بنظر إتقان قواعد اللغة. فتعليم مهارة الكلام يناسب حينما يعلم بالمدخل الاتصالي بأنها مهارة تقتضى على الاتصال بين المتحدثين. تهدف هذه الورقة إلى وصف عملية تعليم مهارة الكلام بالمدخل الاتصالي في المدرسة العالية الإسلامية عباد الرحمن مالانج. تدل نتائج البحث إلى أن إجراء عملية التعليم بالمدخل الاتصالي من البداية إلى النهاية تتضمن من المعلمين الذين يعلمون اللغة العربية بالمدخل الاتصالي، وأهداف تعليم مهارة الكلام بالمدخل الاتصالي الجيد، ومناسبة المادة التعليمية المستخدمة لتعليم مهارة الكلام بالمدخل الاتصالي، ومناسبة أنشطة تعليم مهارة الكلام المستخدمة بالمدخل الاتصالي، وتقويم تعليم مهارة الكلام بالمدخل الاتصالي المستقيم. الكلمات المفتاحية : التعليم، مهارة الكلام، المدخل الاتصالي